Degradable Hydrogel Adhesives with Enhanced Tissue Adhesion, Superior Self‐Healing, Cytocompatibility, and Antibacterial Property. Issue 4 (23rd November 2021) - Yang, Yili; Shi, Kai; Yu, Keman; Xing, Feiyue; Lai, Haiwang; Zhou, Yingshan; Xiao, Pu
Abstract: Degradable hydrogel adhesives with multifunctional advantages are promising to be candidates as hemostatic agents, surgical sutures, and wound dressings. In this study, hydrogel adhesives are constructed by catechol‐conjugated gelatin from natural resource, iron ions (Fe 3+ ), and a synthetic polymer. Specifically, the latter is prepared by the radical ring‐opening copolymerization of a cyclic ketene acetal monomer 5, 6‐benzo‐2‐methylene‐1, 3‐dioxepane and N ‐(2‐ethyl p ‐toluenesulfonate) maleimide. By the incorporation of ester bonds in the backbone and the combination with quaternary ammonium salt pendants in the polymer, it exhibits excellent degradability and antibacterial property. Remarkably, doping the synthetic polymer into the 3, 4‐dihydroxyphenylacetic acid‐modified gelatin network forms a semi‐interpenetrating polymer network which can effectively improve the rigidity, tissue adhesion, and antibacterial property of fabricated hydrogel adhesives. Moreover, non‐covalent bonds from coordination interaction between catechol and Fe 3+ contribute to the fast self‐healing of the developed hydrogel adhesives. These hydrogel adhesives with the multiple merits including the degradability, enhanced tissue adhesion, superior self‐healing, good cytocompatibility, and antibacterial property show the great potential to be used as tissue adhesives in biomedical fields. Abstract : Semi‐interpenetrating polymer networks constructed by catechol‐conjugated gelatin, iron ions, and a synthetic linear polymer can be used as degradable hydrogel adhesives with enhanced tissue adhesion, superior self‐healing, good cytocompatibility, and antibacterial property. The approach to develop the multifunctional hydrogel adhesives with the multiple merits opens a new avenue in biomedical applications.